2017
DOI: 10.1136/bmjopen-2016-013784
|View full text |Cite
|
Sign up to set email alerts
|

Translation of the international outcome inventory for hearing aids into Portuguese from Portugal

Abstract: ObjectiveTo translate the International Outcome Inventory for Hearing Aids (IOI-HA) Questionnaire from English to Portuguese (from Portugal) and to validate this instrument of study on the Portuguese population.DesignIn this prospective study, a translation from English into Portuguese of the IOI-HA was performed, and linguistic adaptation and counter translation were also accomplished. The data were analysed for internal consistency testing for correlations between each individual item and the total score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…The study results support good discriminant validity of the Kannada version of the IOA-HA questionnaire, as each of the correlations (inter-item) were below 0.60 (see Table 5). These results were consistent with previous studies that showed a good discriminant validity of IOI-HA in English and other translated versions (Cox, Stephens, and Kramer 2002;Kramer et al 2002;Pavia et al, 2017). The current study showed poor convergent validity (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The study results support good discriminant validity of the Kannada version of the IOA-HA questionnaire, as each of the correlations (inter-item) were below 0.60 (see Table 5). These results were consistent with previous studies that showed a good discriminant validity of IOI-HA in English and other translated versions (Cox, Stephens, and Kramer 2002;Kramer et al 2002;Pavia et al, 2017). The current study showed poor convergent validity (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The Kannada version of IOI-HA also had acceptable internal consistency (Cronbach's Alpha of 0.7) and test-retest reliability (ICC ¼ 0.71). The internal consistency, as measured using Cronbach's Alpha, was found to be slightly higher; this is similar to the 0.78 consistency in English (Cox and Alexander 2002), 0.83 in Korean (Chu et al 2012), 0.82 in Danish (Jespersen, Bille, and Legarth 2014), 0.84 in Portuguese (Pavia et al, 2017), and 0.77-0.79 in Dutch (Kramer et al 2002). Test-retest reliability in the current study (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It consists of 7 questions, including the time of wearing hearing aids, the benefit and satisfaction of hearing aid applications, etc. Each question is ranging from the worst performance 1 to the best performance 5 [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…In both situations, they are prescribed by an otorhinolaryngologist, although in the NHS the total cost of HAs is subsidized. However, this process is time-consuming and implies that, after the appointment to deliver the hearing aids at the hospital, the fitting and adjustment of HAs is carried out in a private center specialized in HAs, which was selected as a supplier by the hospital [12]. Conversely, when the patients purchase the HAs for themselves, they can choose the brand and type of hearing aid, as well as the supplier.…”
Section: Introductionmentioning
confidence: 99%